2010
DOI: 10.1017/s0950268810000440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization ofStaphylococcus aureusin Lebanon

Abstract: Staphylococcus aureus is an important human pathogen and is a growing public health concern. In this study, 130 S. aureus, 93 methicillin-resistant S. aureus (MRSA) and 37 methicillin-sensitive S. aureus (MSSA), clinical isolates recovered from Lebanon were typed by protein A gene (spa) sequencing and multi-locus sequence typing (MLST). Forty-eight different spa types were identified and clustered into 30 different groups. MLST revealed 10 sequence types (STs) among the isolates. There were eight major MRSA cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
59
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 37 publications
(56 reference statements)
14
59
6
Order By: Relevance
“…All the isolates with t044 (12.2%), as the third most common spa type identified in the current study, were MRSA and belonged to SCCmec IV and some of them (54.5%) were PVL-positive. In line with the results of the present study, spa type t044 PVL-positive MRSA was reported from Sweden (34), UK (32), and Lebanon (35) In accordance with the findings of the present study, in a study conducted by Meemken et al (36) on S. aureus isolated from animals in Germany, spa type t426 was detected in both MRSA and MSSA isolates. These data suggest transmission of MRSA spa type t426 between different hosts (humans and animals).…”
Section: Discussionsupporting
confidence: 93%
“…All the isolates with t044 (12.2%), as the third most common spa type identified in the current study, were MRSA and belonged to SCCmec IV and some of them (54.5%) were PVL-positive. In line with the results of the present study, spa type t044 PVL-positive MRSA was reported from Sweden (34), UK (32), and Lebanon (35) In accordance with the findings of the present study, in a study conducted by Meemken et al (36) on S. aureus isolated from animals in Germany, spa type t426 was detected in both MRSA and MSSA isolates. These data suggest transmission of MRSA spa type t426 between different hosts (humans and animals).…”
Section: Discussionsupporting
confidence: 93%
“…Also, in this study, lukS/F-PV were more frequently observed in SCCmec IVc isolates (94%), but they were not restricted to this cassette type and they were also present in SCCmec types I, IVa and V. Other studies conducted in China (Wu et al 2010) and in USA (Abdel-Haq et al 2009) that have evaluated the epidemiological and molecular features of MRSA and MSSA isolates from children found that the most frequent SCCmec type was IVa and all of these strains carried the lukS/F-PV genes. Also, similar to our findings, results of a study conducted in Lebanon revealed that the PVL genes were present mainly in SCCmec IVc isolates (Tokajian et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The most commonly occurring spa types were t044 and t037. The high prevalence of spa type t044 was in concordance with several other studies including: Vindel et al [19] who showed that this type was widely disseminated in Europe, Tokajian et al [20] reporting that 38% of S. aureus isolates belonged to spa type t044 in Lebanon, and Khalil et al [11] revealing that 18% of MRSA recovered from stool and nose specimens from children in Jordan were of spa type t044. spa type t044 belongs to the one of the recently emerging PVLpositive MRSA strains (ST80-MRSA-IV), known to occur and predominate in certain regions in Europe and in the Middle East [21].…”
Section: Discussionsupporting
confidence: 88%